PENGAMBILAN SUMPAH UNTUK BUKTI BARU DARI TERMOHON PENINJAUAN KEMBALI PERKARA PERDATA - Sobari, Ahmad (NATIONAL JOURNAL of LAW, 2022)
AbstractSubmitting a judicial review (PK) at the Supreme Court, both criminal and civil cases, one of the material requirements is the discovery of new evidence or fresh fact or new circumstances, called novum. The material reason for the Judicial Review (Peninjauan Kembali) of criminal cases is called "new circumstances", contained in Article 263 Paragraph (2) letter a of the Indonesian Criminal Procedure Code. The form of new evidence or novum in civil cases, referred to as "decisive evidence letters", is stated in Article 67 letter b of Law no. 14 of 1985 concerning the Supreme Court in conjunction to Law No. 5 of 2004 in conjunction to Law No. 3 of 2009 concerning the Second Amendment. Although using different terms about the novum (criminal procedure code and civil procedure code), the actual meaning is not different. The difference is that in criminal cases it is not explicitly stated about the evidence/the form of novum, where the novum was obtained, contained or attached. But new evidence or novum in civil cases is expressly called "with documentary evidence", then the new evidence or novum is documentary evidence. In criminal cases, the form of evidence for a novum is not mentioned, so the form of a new situation or novum in a criminal case can be obtained from letter evidence or witnesses. The important thing is that the contents of the novum are in the form of new conditions that previously, when the case was examined at the first level of court, the new circumstances had not been revealed in the trial of the first level court. For applicants for reconsideration (PK) Novum or new evidence in the form of a letter based on Article 69 letter b of Law no. 14 of 1985, since the discovery of the documents of evidence, the day and date of their discovery must be declared under oath and ratified by the competent authority. However, the law (No. 14 of 1985) does not regulate the Novum or new evidence held by the Respondent for Judicial Review, in the form of a counter memory from the Judicial Review with additional new evidence, whether it must be declared under oath and ratified by an authorized official. This can cause problems because of the difference in the strength of the evidence between novum of the Judicial Review of the Petitioner and the Judicial Review of the Respondent. In order to have a legally balanced strength of evidence, it is better if new evidence or novum from the Respondent from the Judicial Review is also regulated in the procedural law, which is sworn in and ratified by an authorized official.Key word: Judicial Review; novum; new evidenc; equality before the law; The power of                    evidence.